Health, family and economic consequences of traumatic brain injury - Białczyk, Katarzyna; Korzycka-Wilińska, Wanda; Gołota, Szymon; Wyszkowska, Zofia (Journal of Education, Health and Sport, 2017)
Traumatic Brain Injury (TBI) is a serious global problem, associated with enormous medical and social costs. The real total cost of TBI is extremely difficult to estimate. It results of the multifaceted nature of this issue and the need to take account of the ever-growing consequences. In the analysis of medical costs problems, we see that it is associeted to the costs of direct traumatic treatment, early rehabilitation, and long-term TBI treatment which leads to a further growth. In addition, TBI is associated with a change in the family functioning, and can lead to affective disorders (especially depression), significantly impairing their further psychosocial functioning. In addition, the consequences of traumatic brain injuries are always associated with an increase in the mental burden of families and carers of patients, which can be another huge medical and social problem. The aim of this paper is to elucidate the neuropsychiatric probles associeted to the TBI and to reveal it’s economic consequences from the perspective of carers of people with TBI.